(untitled) (Journal of the College of Basic Education, 2022)
Leadership in its various operations is a tool for change, development, and progress in all organizations, whether industrial, commercial, or educational. It works to achieve goals by introducing the necessary improvements in administrative organization, employee behavior, means, and leadership styles. An analysis of leadership behavior in organizations Changing its nature and revealing its determinants is a necessity to understand and interpret organizational performance, not only that, but also the methods of managing all human resources and solving problems resulting from their use in order to succeed.